Let y = x^(sin x)
ln y = ln x^(sin x)
ln y = (sin x)(ln x)
(1/y)(dy/dx) = (cos x)(ln x) + (sin x)/x
dy/dx = (cos x ln x + (sin x)/x) (x^(sin x))
2007-11-13 17:17:29
·
answer #1
·
answered by Blake 3
·
0⤊
0⤋
general product rule is:
if you have a function that is the product of two functions of x, for instance, y(x) = f(x) * g(x), then the derivative is:
y'(x) = f(x)*g'(x) + g(x)*f '(x) equation 1
in this case, f(x) = x, and g(x) = sin(x).
so define the derivatives as f'(x) = 1, and g'(x) = cos(x)
Now plug these into equation 1.
y'(x) = x*cos(x) + 1*sin(x), which simplifies to
y'(x) = x*cos(x) + sin(x)
2007-11-13 17:16:31
·
answer #2
·
answered by mikenwu99 3
·
0⤊
0⤋
Think of it as y=x^(sin(x)). Then from this you can apply the ln rule:
lny=lnx^(sin(x))
Where this allows you to bring down the exponent function to get:
lny=(sin(x))lnx
Now, through implicit differentiation you can solve like this:
(1/y)(dy/dx)= cosx(lnx) + (1/x)(sinx)
dy/dx = y* [ cosx(lnx) + (1/x)(sinx) ]
Now you have this substitue in your y-value to get your final derivative functions!:
dy/dx = [x^(sin(x))]*[cosx(lnx) + (1/x)(sinx) ]
2007-11-13 17:18:36
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
y = x^(sin x)
Take the log of both sides.
ln y = ln[x^(sin x)] = (sin x)(ln x)
(1/y)(dy/dx) = (cos x)(ln x) + (sin x)/x
dy/dx = [(cos x)(ln x) + (sin x)/x] y
dy/dx = [(cos x)(ln x) + (sin x)/x] [x^(sin x)]
2007-11-13 18:01:20
·
answer #4
·
answered by Northstar 7
·
0⤊
0⤋